PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KETEPATAN DAN KEAKURATAN PENGUNGKAPAN FORWARD-LOOKING INFORMATION - Afifah Cahya Muliawati; Abdul Rohman (Diponegoro Journal of Accounting, 2018)
The purpose of this paper is to examine the influence of corporate governance on the quality of forward-looking information disclosure in Indonesia which forward-looking information is voluntary disclosure. Forward-looking information will be measured by sales forecast using precision and accuracy to measure the quality of information regarding disclosures in annual reports that are published by firms listed on the Indonesia Stock Exchange (BEI) in 2015. Methods of testing the hypothesis of this study are logistic and multiple regression analysis.The results show that corporate governance has a significant and positive impact on the precision of sales forecast. Firms with good corporate governance tend to disclose their sales forecast precisely rather than qualitative but tend to disclose nonfinancial information in sales forecast. Firms with good corporate governance will provide accurate sales forecast but tend to be optimistic bias.